Delphi Method Analysis and Consensus of Prevalent Distinctive Practices for Biliary Atresia Management after Kasai Portoenterostomy - Sravanthi Vutukuru; Shailesh Solanki; Ravi Prakash Kanojia (Wolters Kluwer Medknow Publications, 2024)
Background: Extrahepatic biliary atresia (BA) is seen in infants, with an incidence of 1 in 15,000 live births. The presentation is progressive jaundice, dark-colored urine, and clay-colored stools. Kasai portoenterostomy (KPE) is the commonly performed surgical procedure in these patients. Postoperatively, phenobarbitone, ursodeoxycholic acid (UDCA), steroids, and other drugs are given to improve bile drainage and prevent inflammation and fibrosis. However, a definitive protocol regarding the need for different drugs, dosage, and duration varies across individual surgeons and centers. No universally accepted protocol exists for postoperative management after KPE. Aim: The aim of this study was to know the prevailing postoperative management of BA by subject experts and use the Delphi process to know if the experts want to change their practice based on the results from the survey. Material and Methods: A questionnaire was made after discussing with two experts in the field of BA. The questionnaire was mailed to 25 subject experts. The first survey data were analyzed and shared with all responders. In the second survey, change in the management based on the results from the first survey was assessed. Results: The Delphi questionnaire was answered by 17 experts. Postoperatively, prophylactic antibiotics are prescribed for 6-12 weeks by around 40% and >12 weeks by 30% of respondents. Phenobarbitone is prescribed for <3 months by nearly 50%. UDCA is prescribed for <3 months, ≤6 months, and 6 months-1 year by 47.1%, 23.5%, and 23.5% responders, respectively. Nearly 50% prescribe steroids (mostly prednisolone), and among them, two-thirds prescribe it for 6-12 weeks. Approximately 60% give antiviral drugs to children who are cytomegalovirus immunoglobulin M positive. In our survey, 50% of experts perform 5-10 KPE per year, and 25% each perform 10-15 and >15 KPE per year. The second survey noted that a significant percentage of responders want to change their practice according to consensus. Conclusion: From our Delphi survey, an overview of the postoperative management of BA could be made. However, multicentric studies are required for uniform protocol on the postoperative management of BA.